2017
DOI: 10.1007/s11104-017-3381-z
|View full text |Cite
|
Sign up to set email alerts
|

Residual effect of BNI by Brachiaria humidicola pasture on nitrogen recovery and grain yield of subsequent maize

Abstract: Background and Aims The forage grass Brachiaria humidicola (Bh) has been shown to reduce soil microbial nitrification. However, it is not known if biological nitrification inhibition (BNI) also has an effect on nitrogen (N) cycling during cultivation of subsequent crops. Therefore, the objective of this study was to investigate the residual BNI effect of a converted long-term Bh pasture on subsequent maize (Zea mays L.) cropping, where a long-term maize monocrop field (M) served as control. Methods Four levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 45 publications
4
55
1
Order By: Relevance
“…In this regard, Moreta et al (2014) and Karwat et al (2017) found that the BNI effect of Bh on soil nitrifier activity could persist for at last one year after replacement of the pasture with maize. Gopalakrishnan et al (2007) reported several compounds with BNI activity in the root tissue of Bh, and our data suggest that there could be important allelic interactions within the biparental population related with the synthesis/accumulation of BNI compounds that could be exploited further through breeding to combine the high BNI potential with improved forage productivity and nutritional quality (Mackay et al 2009).…”
Section: The Bni Activity In the Biparental Populationmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, Moreta et al (2014) and Karwat et al (2017) found that the BNI effect of Bh on soil nitrifier activity could persist for at last one year after replacement of the pasture with maize. Gopalakrishnan et al (2007) reported several compounds with BNI activity in the root tissue of Bh, and our data suggest that there could be important allelic interactions within the biparental population related with the synthesis/accumulation of BNI compounds that could be exploited further through breeding to combine the high BNI potential with improved forage productivity and nutritional quality (Mackay et al 2009).…”
Section: The Bni Activity In the Biparental Populationmentioning
confidence: 97%
“…High BNI genotypes of Bh are capable of suppressing N2O emission from N inputs, e.g. animal excreta (Byrnes et al 2017) and it has been shown that they improve the NUE of a subsequent maize crop (Moreta et al 2014;Karwat et al 2017). Commercial cultivars of Brachiaria species are important for Latin American livestock production, the main economic activity in this region (Miles et al 2004;Rivas and Holmann 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Potential nitrification rate (PNR) was estimated by aerobic soil incubation with the 174 methods described by Byrnes et al (2017) and Karwat et al (2017). The PNR assay has been 175 demonstrated to be a useful method to test the BNI activity in soils under different Brachiaria 176 genotypes (Nuñez et al 2018).…”
Section: Soil Microbial Biomass and Phosphomonoesterase Activity 156mentioning
confidence: 99%
“…By preventing the microbial transformation of less soil mobile to more soil mobile nitrate ( ), BNI is expected to reduce leaching of nitrogen (N) from ecosystems ( Subbarao et al, 2009 , 2013 ; Coskun et al, 2017b ). Recent research has been undertaken to investigate the BNI effect by Bh on N dynamics, for example on the reduction of nitrous oxide (N 2 O) emissions from soils ( Byrnes et al, 2017 ), or on the influence of residual BNI effect on N uptake of subsequent crops ( Karwat et al, 2017 ). However, indicators for reduced leaching losses by effective BNI do not exist yet.…”
Section: Introductionmentioning
confidence: 99%